Evidence of increased fecal granins in children with irritable bowel syndrome and correlates with symptoms. Issue 1 (9th October 2018) - Shulman, Robert J.; Öhman, Lena; Stridsberg, Mats; Cain, Kevin; Simrén, Magnus; Heitkemper, Margaret
Abstract: Background: Granins have been implicated in the pathophysiology of irritable bowel syndrome (IBS) in adults. We sought to determine whether fecal granins are altered in children with IBS and associated with symptoms. Methods: Children (7‐12 years of age) with IBS and healthy controls (HC) kept daily pain and stool diaries for 2 weeks. Stool samples were analyzed for chromogranins A and B (CgA, CgB) and secretogranins II and III (SgII, SgIII). Children also completed psychological measures to assess anxiety, depression, somatization, and internalizing symptoms. Key Results: Fecal CgB and SgIII concentrations were higher in all the boys (IBS plus HC, n = 48) than in all the girls (IBS plus HC, n = 75) ( P  = 0.02 and P  = 0.046, respectively). CgA and SgIII were greater in children with IBS (n = 52) vs HC (n = 69) ( P  = 0.01, P  = 0.017, respectively). CgB and SgII did not differ between groups. In children with IBS, the number of pain episodes per week and mean daily pain rating correlated positively with all four granins. The number of stools per day correlated positively with CgB and SgII, and the percent of diarrheal stools (6 or 7 on the Bristol Scale) correlated inversely with all four granins in boys but not in girls. Fecal granins did not correlate with psychological measures. Conclusions and Inferences: As measured by fecal granins, there is evidence of neuroimmune activation in children with IBS. Granins are related to abdominal pain symptoms, stooling frequency, and stool form in children with IBS. Sex influences the fecal concentration of CgB and SgIII. Abstract : As measured by fecal granins, there is evidence of neuroimmune activation in children with IBS. Granins are related to abdominal pain symptoms, stooling frequency, and stool form in children with IBS. Sex influences the fecal concentration of certain granins.